TiO2- CuI Nanoparticle /Ru Solid State Dye-Sensitize Solar Cells - taha, samar; Al-Dabag, Samer. Y.; Ahmed, Sudad. S.; Taher, Wasan. J. (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
In this workÂ solid state dye sensitized solar cell (SSDSSC) type Â (ITO / TiO2/ Ru / CuI / Ag) is fabricated. The thin films are prepared by pulse laser deposition (PLD) technique under the vacuum pressure of 3Ã—10âˆ’3Â mbar and annelid at 450 oC. In this techniqueÂ Nd:YAG laser at 1064 nm wavelength with (200 , 500 , 800) pulsed was used. It was noticed from (I-V) characteristics of the solar cell that Â the photocurrentÂ collectedÂ fromÂ theÂ TiO2Â (NP)Â is increase as the number of Â laser pulses increase. The conversion efficiency of TiO2 is increased Â from 2.115%Â upÂ toÂ 5.654% and for CuI from 1.73 % to 5.19 % when the number of pulses increase from 200 up to 800.